Pressure drop and heat transfer characteristics of a high-temperature printed circuit heat exchanger. (5th September 2016) - Chen, Minghui; Sun, Xiaodong; Christensen, Richard N.; Skavdahl, Isaac; Utgikar, Vivek; Sabharwall, Piyush
Highlights: Pressure drop and heat transfer characteristics of a high-temperature printed circuit heat exchanger have been obtained. Comparisons of experimental data and available correlations have been performed. New Fanning friction factor and heat transfer correlations for the test PCHE are developed. Abstract: Printed circuit heat exchanger (PCHE) is one of the leading intermediate heat exchanger (IHX) candidates to be employed in the very-high-temperature gas-cooled reactors (VHTRs) due to its capability for high-temperature, high-pressure applications. In the current study, a reduced-scale zigzag-channel PCHE was fabricated using Alloy 617 plates for the heat exchanger core and Alloy 800H pipes for the headers. The pressure drop and heat transfer characteristics of the PCHE were investigated experimentally in a high-temperature helium test facility (HTHF) at The Ohio State University. The PCHE helium inlet temperatures and pressures were varied up to 464 °C/2.7 MPa for the cold side and 802 °C/2.7 MPa for the hot side, respectively, while the maximum helium mass flow rates on both sides of the PCHE reached 39 kg/h. The corresponding maximum channel Reynolds number was approximately 3558, covering the laminar flow and laminar-to-turbulent flow transition regimes. New pressure drop and heat transfer correlations for the current zigzag channels with rounded bends were developed based on the experimental data. Comparisons between the experimental data and the results obtained from the available PCHE and straight circular pipe correlations were conducted. Compared to the heat transfer performance in straight circular pipes, the zigzag channels provided little advantage in the laminar flow regime but significant advantage near the transition flow regime.